Evaluasi Laporan Pertanggung Jawaban pada Kontrak Asuransi Berdasarkan PSAK 108: Studi Kasus PT Allianz Life Indonesia Vision Batu Bara Mdn 138 - Apriliani, Nurhalimah; Harmain, Hendra; Harahap, Rahmat Daim (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Statement of Financial Accounting Standards (PSAK) 108 is an accounting standard that is used as a guide for accountants in the recognition, measurement and presentation of sharia insurance transactions. This research aims to produce financial reports that are accurate, reliable and relevant so as to make people believe in the company. The method used in this study uses a qualitative descriptive research method. The subject of this research is the administrative and financial staff of PT. Allianz, which records company transactions. Analysis that is based on the notions or facts as they are in a systematic and accurate way. Data analysis techniques include data reduction, data presentation, and drawing conclusions. Based on the results of the research that has been done, it can be concluded that the Evaluation of Liability Reports on Insurance Contracts at PT. Allianz Life Indonesia Vision Coal MDN 138 The company accepts premium payments and develops business activities with a purely profit orientation, ignoring several syar'i prohibitions such as the elements of maisir, gharar and usury. Compliance with PSAK in sharia insurance contracts in companies that comply with financial rules according to accounting standards, despite the fact that much remains to be evaluated in terms of insurance claims. Keywords : Liability Report, Insurance Contract, PSAK 108.